Penatalaksanaan Diabetes Mellitus Tipe 2 Dengan Hipertensi Grade 1 Pada Perempuan Usia 50 Tahun dengan Pendekatan Kedokteran Keluarga - Nisa Arifah; Reni Zuraida (Medula, 2020)
Indonesia is the 7th country with the highest prevalence of diabetes,90% of patients who suffer from diabetes mellitus (DM) throughout the world are DM type 2. Preparation of Medical Base Evidence-based tasks in male patients with risks and problems as well as patient management based on patient responsibility and centralized and family patient approach. This study is a case report. Primary data were obtained through anamnesis (autoanamnesis), physical examination, and home visits. Secondary data obtained from the patient's medical records. Assessment is based on diagnosis from the beginning, process, and end of qualitative and quantitative studies. Mrs. W 50 years old patient was diagnosed with Diabetes Mellitus Type 2 accompanied by hypertension. Patients have aspects of internal risk in the form of patients having a poor diet, patients having poor lifestyle, lack of knowledge of patients about controlling and monitoring DM, family history factors of hypertension, and patients' curative treatment. External aspects of the family psychosocial risk in the form of a lack of understanding of the patient's disease, as well as patient family members less motivating patients to maintain a regular diet according to the DM diet, controlling blood sugar and blood pressure, and regular treatment. Holistic management with a family doctor approach can improve knowledge, attitudes, and behavior in patients. Also, the role of the family is very important in the care and treatment of sick family members.